5(2x+8)=-23+53

Simple and best practice solution for 5(2x+8)=-23+53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+8)=-23+53 equation:



5(2x+8)=-23+53
We move all terms to the left:
5(2x+8)-(-23+53)=0
We add all the numbers together, and all the variables
5(2x+8)-30=0
We multiply parentheses
10x+40-30=0
We add all the numbers together, and all the variables
10x+10=0
We move all terms containing x to the left, all other terms to the right
10x=-10
x=-10/10
x=-1

See similar equations:

| 11x=15x+16 | | 33=-7+5x | | -19+p=5(7-5p)-2 | | 18a-9a=9 | | 4(5x+8)=-44+36 | | 7t+35+(10.5-+t)=308 | | 3x-11+x7=180 | | 5h-4=26 | | 8x+78+2x+114=90 | | (5/8x+61/4)-10=0 | | N2-5n=0 | | 8r+8=4(r+6) | | 18.10x+183.75=14.59(x+15) | | (x-100)/(x)=0.8 | | 10-8(2x+4)=10 | | 18.10x+183.75=14.59(x+15 | | (2x+29)=(9x-13) | | -2-n=7+2n | | 312+3x=340 | | 3x+5x-9=2(4x+1) | | y=17-4(4) | | (x-100)/x=0.8 | | 5x+3+7x=14x-19 | | 150=140.94+0.49m | | -2(4x+8)-(2(-4+2x)=-8 | | 7t+35+(10.5-+t)+35=308 | | 4m^2-m-5=0 | | 5x(x-2)-2x^2x=-2 | | 8+51x+4=55x+7+x | | 2n-6=5n+6 | | 6x+5-4x=4x+45-4x | | -20-1(-37)=x/7 |

Equations solver categories